GAMBARAN UPAYA PENGENDALIAN HIPERTENSI DI WILAYAH KERJA PUSKESMAS WORI PADA MASA PANDEMI COVID 19 - Tammy Clara Beatrix Wulur; Mario Katuuk; Sefti Rompas (JURNAL KEPERAWATAN, 2022)
Background: hypertension is a disease that is often found in health services. The prevalence of hypertension in the Wori Health Center working area has increased amid the covid 19 pandemic situation and conditions. Objective: this study is to determine the description of hypertension control efforts in the Wori Health center working area during the covid 19 pandemic. Method: the research used is descriptive quatitative survey approach and the sample in this study amounted to 156 respondents. Results: showed that of the 156 respondents (41.7%) had a fairly compliant compliance rate, 47 respondents (30.1%) were compliant, and good diet compliance rate as many as 89 respondents (57.1%), light physical avtivity as many as 56 respondents (35.9%), high physical activity as many as 51 respondents (32.7%) and moderate physical activity as many as 89 respondents (57.1%) and low smoking behaviour as many 67 respondents (42.9%). Conclusion: the results of this study illustrate the efforts to control hypertension in the Wori Health Center working area during the covid 19 pandemic starting from diet, physical activity, smoking behaviour and medication adherence.